Antimicrobial therapy for asymptomatic bacteriuria or candiduria in advanced cancer patients transitioning to comfort measures. (1st March 2019) - Datta, Rupak; Wang, Tianyun; Zhu, Mojun; Dembry, Louise Marie; Han, Ling; Allore, Heather; Quagliarello, Vincent; Juthani-Mehta, Manisha
Abstract: Among 300 advanced cancer patients with potential urinary tract infection (UTI), 19 had symptomatic UTI. Among remaining patients (n = 281), 21% had asymptomatic bacteriuria or candiduria, and 14% received inappropriate therapy for 279 antimicrobial days. Bacteriuria or candiduria predicted antimicrobial therapy. At 10, 000 to <100, 000 CFU/mL, the incidence rate ratio [IRR] was 16.9 (95% confidence interval [CI], 6.0–47.2), and at ≥100, 000 CFU/mL, the IRR was 27.9 (95% CI, 10.9–71.2).